Two overlooked species of Ipomoea L. (Convolvulaceae) from Paraguay - Wood, J; de Arrúa, R; de Rojas, G; Scotland, R (Springer, 2016)
The Paraná region of eastern Paraguay is highlighted as the centre of a radiation in Ipomoea species, of which I. malvaeoides is the best known and arguably the most variable. A key to frequently confused Paraguayan species in this complex is provided. A new species, I. itapuaensis J. R. I. Wood & R. Degen is described and I. malpighipila O’Donell var.aemilii O’Donell is raised to specific status as I. aemilii (O’Donell) J. R. I. Wood & R. Degen. The two species are illustrated and their characteristics, distribution and conservation status are discussed.